Economic Opportunity and Youth Migration: Evidence from Nepal - Maharjan, Milan; Thapa-Parajuli, Resham (Economic Journal of Nepal, 2024)
Youth migration has become a defining feature of Nepal’s demography, characterized by both mass emigration and significant internal migration. This research explores whether heterogeneity in economic opportunities across districts in Nepal plays a role in migration patterns in Nepal. The magnitude of migration is measured by calculating district-level net migration rates between 2011 and 2021 for the 20–30 age group (in 2021) using the Life Table Survival Ratio (LTSR) method. The impact of district-level per capita income on the net migration rate is then estimated using Two-Stage Least Squares, with the land productivity index serving as an instrument for per capita income. The land productivity index is derived for each district using principal component analysis of land productivity for major cereal and cash crops. The finding reveals that regions with better economic opportunities gain the youth population, while those with fewer opportunities lose them. This result underscores the importance of generating economic opportunities to address youth migration trends.